2018
DOI: 10.1002/mus.26049
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolitional assessment of tibialis anterior force and architecture during critical illness

Abstract: Muscle weakness was evident at ICU admission. No additional decrements were observed 7 days later despite significant reductions in muscle size. These data suggest that not all ICU weakness is truly "acquired" and questions our understanding of muscle function during critical illness. Muscle Nerve 57: 964-972, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…22 Four studies reported foot positioning; toes facing the roof. 8,19,36 Neutral rotation/positioning of the lower limbs was reported by five authors 12,15,23,33,37 and external rotation of the lower limb by one. 32…”
Section: Patient Population and Study Designmentioning
confidence: 96%
See 2 more Smart Citations
“…22 Four studies reported foot positioning; toes facing the roof. 8,19,36 Neutral rotation/positioning of the lower limbs was reported by five authors 12,15,23,33,37 and external rotation of the lower limb by one. 32…”
Section: Patient Population and Study Designmentioning
confidence: 96%
“…17,21,22,[27][28][29][30][31] Mueller et al and Turton et al referenced the head of bed at a 30 and 45 elevation, respectively, 16,32 while one paper reported a 30 -45 head of bed elevation, 19 and another referenced semi-supine positioning. 33 The term 'limb extension' was reported by 21 studies. 5,8,[12][13][14][15][16]19,[23][24][25][26][33][34][35][36][37][38][39][40][41] One paper referenced 'legs flat' and was not included as referencing extension.…”
Section: Patient Population and Study Designmentioning
confidence: 99%
See 1 more Smart Citation
“…This is 371 perhaps unsurprising given the complex relationship between nutritional status and 372 muscle mass, muscle quality, muscle strength and physical function that is non-373 linear. Indeed, an improvement in muscle quantity may not translate to a proportional 374 improvement in volitional, or non-volitional, force production (46), and in turn a 375 commensurate change in performance of physical function, which additionally requires coordination of cognitive and executive function. Furthermore, establishing 377 a true baseline of physical functional status is challenging in the absence of robust 378 markers to determine pre-morbid ability.…”
Section: Publication Bias 341mentioning
confidence: 99%
“…markers of inflammation versus days since admission). This is particularly pertinent when considering trials of nutrition and exercise where the biological interaction between these interventions may be uncoupled early in critical illness [19], and are likely to only be effective once this is recoupled [20]. Work has begun within the epoch between ICU discharge and hospital discharge, an area with little data and where interventions are far more likely to be effective as the confounders of inflammation, hypoxia and multi-organ failure have subsided [21,22].…”
Section: Signal-to-noise Ratiosmentioning
confidence: 99%